Photosynthetic Response Under Long-Term Drought Stress in Somatic Hybrids Between Potato and “Solanum Bulbocastanum” - DÉNES, Tünde-Éva; ERDELY-MOLNÁR, Imola; MUSTAȚĂ, Raluca Alina; VASS, István; CSERI, András; VASS, Imre; RAKOSY-TICAN, Elena (Studia Universitatis Babeș-Bolyai Biologia, 2016)
Potato (Solanum tuberosum) is a sensitive plant to biotic and abiotic stress, some of the main stress factors affecting potato yield being the drought stress and the late blight disease caused by Phytophthora infestans. In order to obtain resistant cultivars to late blight somatic hybrids between cultivated potato and Solanum bulbocastanum, carrying two broad spectrum resistance genes against late blight (Rpi-blb1 and Rpi-blb3), were produced previously by protoplast electrofusion (Rákosy-Tican et al., 2015). Somatic hybrids which proved to be resistant to late blight were screened also for drought stress tolerance and the long-term drought stress effect on the plant photosynthesis was verified.